Pedagogical Process and Issues of Learning Social Studies at Upper Primary Schools in a Slum Area of Maharashtra - Sethy, Premananda (JOURNAL OF INDIAN EDUCATION, 2021)
The objective of this paper is to analyse the classroom observation and insight of the teachers during the social studies teaching-learning process at upper primary schools nearby slum dominated area of Mumbai Urban and Suburban district of Maharashtra State. The main focus of classroom observation was to discuss the problems of teachers and students during social studies pedagogical practices and process with regards to involvement of learners, use of different strategies, assessment and feedback practices, assess the joyful learning, use of TLM and ICT integration in teaching–learning process. The data triangular method was used for theme-wise analysis of pedagogical process from three different characteristics of sample schools under study. It is found that teachers faced problem in communicating the content of social studies, rare participation of students in group activities, too meek to ask question and clear doubt in classroom even provided the freedom and opportunities to students, more specifically who belongs to socio-economic backwards area of slum students. It is suggested that teachers must highlight the connection between text and context and also they should provide space for articulation of thoughts of students in the classroom through various student-centric activities. The importance would be given to those teachers who are significantly dealing with the classroom situation in a democratic way by providing equal opportunity to all the students, more over to those who belongs to slums and underprivileged section of society.